Matricellular Protein Periostin Promotes Pericyte Migration in Fibrotic Airways - Bignold, Rebecca E.; Johnson, Jill R. (Frontiers in Allergy, 2021)
Periostin is a matricellular protein used as a biomarker for asthma. However, its contribution to tissue remodelling in allergic asthma is currently unknown. We previously demonstrated that tissue-resident mesenchymal stem cells known as pericytes are a key cell type involved in airway remodelling, caused by the uncoupling of pericytes from the microvasculature supporting the large airways and facilitated by inflammatory growth factors and cytokines. It is hypothesised that periostin may be produced by profibrotic pericytes and contribute to the remodelling observed in allergic asthma. Lung sections from mice with allergic airway disease driven by exposure to house dust mite (HDM) were stained using an anti-periostin antibody to explore its expression. Human pericytes were cultured and assessed for periostin expression. Migration assays were performed using human pericytes that were pretreated with TGF-β or periostin. ELISAs were also carried out to assess periostin expression levels in bronchoalveolar lavage fluid periostin secretion by pericytes induced by IL-13. Pericytes robustly expressed periostin, with increased expression following treatment with TGF-β. Migration assays demonstrated that pericytes treated with periostin were more migratory. Periostin production was also increased in HDM-exposed mice as well as in pericytes treated with IL-13. Periostin is produced by pericytes in response to TGF-β or IL-13, and periostin plays a key role in inducing pericyte migration. The increase in periostin expression in TGF-β or IL-13 treated pericytes suggests that IL-13 may trigger periostin production in pericytes whilst TGF-β modulates periostin expression to promote pericyte migration in the context of tissue fibrosis.